The Influence of Pre-Mortem Conditions on Pale, Soft and Exudative (PSE) and Dark, Firm and Dry (DFD) Pork Meat - Čobanović Nikola1 (Sciendo, 2016)
The aim of this study was to determine the effect of gender, stocking density in the transport vehicle, lairage time and season on the incidence of skin lesions on pig carcasses and PSE and DFD meat. Skin lesions on carcasses (480, in total) were assessed according to the Welfare Quality® protocol (2009). The pH and temperature measurements were performed 45 minutes after slaughter. The group of carcasses with skin lesions score 2 had significantly higher incidence of PSE and DFD meat compared to the groups of carcasses with skin lesions score 0 and 1. With regard to gender, there were no differences in meat quality parameters, as well as for the incidence of skin lesions and PSE and DFD meat. The results showed that a space allowance lower than 0.3 m2/100 kg and higher than 0.5 m2/100 kg pig had a detrimental effect to animal welfare and meat quality. Lairage time affected meat quality parameters, incidence of skin lesions score and PSE and DFD meat, where after long lairaging (> 17 h) mean pH45 and t45 values became significantly higher, as well as the incidence of skin lesions and DFD meat. After short lairaging (< 1 h) mean pH45 value became significantly lower, while mean t45 value and the incidence of PSE meat became significantly higher. A significantly higher number of skin lesions on the carcass were observed in winter compared to all other seasons. High temperatures during summer and low temperatures during winter had a negative influence on meat quality parameters and incidence of PSE and DFD meat.